The Impact of Behavioral Intervention on Obesity Mediated Declines in Mobility Function: Implications for Longevity. (16th October 2011) - Nocera, Joe; Buford, Thomas W.; Manini, Todd M.; Naugle, Kelly; Leeuwenburgh, Christiaan; Pahor, Marco; Perri, Michael G.; Anton, Stephen D.
Abstract : A primary focus of longevity research is to identify prognostic risk factors that can be mediated by early treatment efforts. To date, much of this work has focused on understanding the biological processes that may contribute to aging process and age-related disease conditions. Although such processes are undoubtedly important, no current biological intervention aimed at increasing health and lifespan exists. Interestingly, a close relationship between mobility performance and the aging process has been documented in older adults. For example, recent studies have identified functional status, as assessed by walking speed, as a strong predictor of major health outcomes, including mortality, in older adults. This paper aims to describe the relationship between the comorbidities related to decreased health and lifespan and mobility function in obese, older adults. Concurrently, lifestyle interventions, including diet and exercise, are described as a means to improve mobility function and thereby limit the functional limitations associated with increased mortality.